The ideal use of the internet and academic success: Finding a balance between competences and knowledge using interval multiobjective programming - Prieto-Latorre, Claudia; Lopez-Agudo, Luis Alejandro; Luque, Mariano; Marcenaro-Gutierrez, Oscar David (Socio-economic planning sciences, 2022)
Young people are increasingly spending more time connected to the Internet. However, it is not clear how this tool associates with students’ academic achievement. In this research, the association between the use of the Internet and different measures of academic performance is explored, in order to define the profile of those students who attain a balanced academic achievement and, in this process, make an ideal use of the Internet. To this aim the methodological approach combines regression analysis based on a census data of 8th grade students in Andalusia (the most populated region in Spain) as well as interval multiobjective programing techniques. Our main finding is that, in order to simultaneously achieve a balanced performance in the four measures of academic achievement, students should use the Internet on a weekly basis for reading and doing school tasks, but should not use the Internet for social networks. •Students should use the Internet on a weekly basis for reading and doing school tasks.•Significant negative relationship between the use of social network sites and academic performance.•Interval multiobjective programming allows obtaining the profile of the student who achieves a balanced performance.